2012
DOI: 10.1021/nn3020322
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Size and ζ-Potential Measurements of Individual Nanoparticles in Dispersion Using Size-Tunable Pore Sensors

Abstract: The prospect of characterizing individual nanoparticles, molecules, or DNA base pairs has generated considerable interest in resistive pulse sensing. In addition to size and concentration analysis, this technique also has the capacity to measure the charge density of objects in situations where electrophoretic forces dominate their motion. Here we present a methodology to simultaneously extract, via appropriate theoretical models, the size and ζ-potential of objects from the resistive pulse signal they generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
247
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(257 citation statements)
references
References 30 publications
8
247
0
2
Order By: Relevance
“…Furthermore, as v P is dependent on v F and v E , characterizing and controlling the magnitude of these components is critical to using pore sensors to measure the ¦-potential of particles. 13 In conclusion, it was shown that particle velocity could be controlled by tuning the pore dimensions of a conical elastic pore sensor via stretching the pore membrane. Stretching the membrane resulted in an increase in the fluid velocity component, but it did not affect the electrokinetic component acting on particles in the pore.…”
mentioning
confidence: 91%
“…Furthermore, as v P is dependent on v F and v E , characterizing and controlling the magnitude of these components is critical to using pore sensors to measure the ¦-potential of particles. 13 In conclusion, it was shown that particle velocity could be controlled by tuning the pore dimensions of a conical elastic pore sensor via stretching the pore membrane. Stretching the membrane resulted in an increase in the fluid velocity component, but it did not affect the electrokinetic component acting on particles in the pore.…”
mentioning
confidence: 91%
“…A relatively recent technology to be developed for the characterisation of nanoparticles is based upon tunable resistive pulse sensing (TRPS) [44][45][46][47][48][49][50][51] . TRPS is based on polyurethane elastomeric membranes in which the pore geometry can be altered in real time.…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential of each particle can then be obtained from the measured electrophoretic mobility using the Smoluchowski approximation 44,57 . The calculated zeta potential only depends on the measured pulse duration and is independent of the magnitude of the pulse, meaning that simultaneous size and charge measurements can easily and reliably be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Tunable resistive pulse sensing (TRPS) [7][8][9][10][11][12][13][14] is a relatively recently-developed nanoparticle characterisation technique. Protocols have been developed for the use of TRPS to measure particle concentrations [7,8], size distributions [9] and charge [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Protocols have been developed for the use of TRPS to measure particle concentrations [7,8], size distributions [9] and charge [10,11]. TRPS is based on the Coulter principle, so that individual particles are detected while in aqueous suspension.…”
Section: Introductionmentioning
confidence: 99%